Alterations in mRNA level of proteins related to redox state and mitochondria in an Alzheimer’s disease animal model: Promising targets in neuroprotection - Sylwia Żulińska; Przemysław L. Wencel; Kinga Czubowicz; Joanna B. Strosznajder (Folia Neuropathologica)
Oxidative stress and disturbances of mitochondrial function in the brain play a crucial role in Alzheimer’s disease (AD). However, little is known about the dynamics of these changes in different parts of the brain at the early stage of AD. This study aimed to determine the expression of genes encoding superoxide dismutases (SOD1, SOD2), poly(ADP-ribose) polymerases (PARPs) and sirtuins (SIRTs). Moreover, transcription of genes related to mitochondrial electron transport complexes (ETC) and biogenesis in the brain cortex of 4-, 6- and 12-month-old transgenic AD Tg mice was analyzed. We observed significant decreases in mRNA of Sod2, Parp1 and Sirt1 in the 3-month-old AD Tg mice and upregulation of Parp1 in the 6-month-old AD Tg mice by qPCR analysis. Then, mt-CytB and mt-Co1 (complex III and IV) mRNA levels were increased in 12- and 6-month-old AD brains, respectively. These changes were linked to lower cytochrome c oxidase activity in 3- and significantly in 6-month-old AD Tg mice. Moreover, transcription of several genes involved in mitochondria biogenesis, such as Nfe2L2 and Tfam, was upregulated respectively in the 3- and 6-month-old AD Tg mice. Expression of genes encoding PGC1 and NRF2 was significantly downregulated in 12-month-old AD Tg mice. In summary, our data identified significant changes in gene expression of Sod2, Parp1 and Sirt1 at an early age (3-6-month-old AD mice) then Ppargc1, Nfe2L2 and Sirt1 at a later age. Recognizing these alterations may be important in better understanding the complexity of pathology in AD. Moreover, our results could be helpful in consideration of appropriate target(s) in neuroprotection.